En-lutar pela memória : uma escrita etnopsicanálitica do luto a partir da experiência de Brumadinho — MG - Izabella Maria de Carvalho Chaves (2024)
This study focused on the theme of mourning resulting from a tragic event marked by social and historical violations, choosing as its object of research the collapse of the B1 ore dam at the Feijão Mine, owned by Vale S.A., in Brumadinho/MG. In the light of psychoanalysis, we investigated the modes of subjectivation of collective loss and the expression of suffering in the face of interventions marked by the contemporary dialectic of immediacy and the predominance of the capitalist and neoliberal model in the city. As a methodology, we used ethnographic field research, a literature review and a survey of data pertinent to the subject. At the end of the study and analysis, we concluded that there is a political, governmental and business tendency to insert neoliberal ideals into the city and its culture as a means of perpetuating violence and consequently an attack on the grieving process. As a way out, we understand that promoting a space for speech, encouraging the strengthening of collectivity, the preservation and creation of social and cultural signs through memory and guided by psychoanalytic ethics, are ways of guaranteeing a symbolic space, beyond the formal analytical setting. Actions that allow for the re-signification of the traumatic and the crossing over of mourning in favor of social transformation as a means of resisting violence and putting a stop to its repetition.